Impact of Sex and Smoking on the Efficacy of EGFR-TKIs in Terms of Overall Survival in Non-small-Cell Lung Cancer: A Meta-Analysis - Xiao, Jian; Zhou, Liang; He, Bixiu; Chen, Qiong (Frontiers in Oncology, 2020)
Background: To comprehensively understand the impact of sex and smoking on the efficacy of epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) therapy in terms of overall survival (OS) in non-small-cell lung cancer (NSCLC). Methods: PubMed, Cochrane Library, Embase, and Scopus were searched from inception to March 17, 2019. OS was analyzed based on hazard ratios (HRs) and 95% confidence intervals (CIs) and estimated using the random effects model. Results: Our meta-analysis included 22 studies involving 11,874 patients. In the primary analysis, we found no statistically significant efficacy difference for EGFR-TKI intervention between females and males (pooled HR 0.95, 95% CI 0.87-1.04, P=0.30) and no obvious efficacy difference between never smokers and ever smokers (pooled HR 0.91, 95% CI 0.76-1.09, P=0.31). In the subgroup analysis of placebo control treatment, we found that female NSCLC patients who received EGFR-TKI therapy had a longer OS than male patients (pooled HR 0.86, 95% CI 0.75-1.00, P=0.04), while smoking status showed no significant effect on the efficacy of EGFR-TKI treatment in terms of the OS of NSCLC patients in all subgroup analyses. Conclusion: The efficacy of EGFR-TKI therapy for NSCLC patients is independent of smoking status but dependent on sex, and females have a longer OS than males.